On the Quantity and Quality of Girls : Fertility, Parental Investments, and Mortality - Anukriti, S. (Oxford University Press, 2021)
Access to prenatal sex-detection technology in India has led to a phenomenal increase in abortion of girls. We find that it has also narrowed the gender gap in under-5 mortality, consistent with surviving girls being more wanted than aborted girls. For every three aborted girls, one additional girl survived to age five. Mechanisms include moderation of son-biased fertility stopping and narrowing of gender gaps in parental investments. However, surviving girls are more likely to be born in lower status families. Our findings have implications not only for counts of missing girls but also for the later life outcomes of girls.